The Effect Of Social Support On Academic Stress - Novi Hidayat (Eudaimonia Journal Psychology, 2025)
Academic stres is a widespread problem among university students and increases the risk of burnout and mental health problems. College students' stres levels depend on many factors, such as social support that serves as a buffer against stres. Gaining more insight into the influence of social support on the relationship between academic stres and burnout can be useful for creating supportive interventions for students in academic contexts. Therefore, this study aimed to examine the influence of social support on academic stres in students. The subjects of this study were junior high school students with a total of 80 respondents obtained by simple random sampling technique. To measure academic stres, and social support with the reliability of the academic stres scale (Cronbach alpha = 0.806), and social support scale (Cronbach alpha = 0.772), with data analysis using simple linear regression analysis. The results showed that social support is related to academic stres. This study shows the importance of conducting further research to increase our understanding of stres and burnout in college students and provide more insight into the influence of various dimensions of social support on the relationship between stres and burnout. This may assist in developing focused interventions to support mental health and academic achievement.